Frequência de arritmias ventriculares após injeção intracoronária de células-tronco da medula óssea em pacientes com cardiomiopatia chagásica - Marques, Adriana Sebba Barroso de Souza (2013)
Background: Treatment with stem cells in various cardiomyopathies may be related to the increase in arrhythmias. Objective: To determine whether intracoronary injection of stem cells in patients with Chagas cardiomyopathy is associated with increased frequency of ventricular arrhythmias, compared to the control group. Methods: A retrospective cohort study that evaluatedt he medical records of 60 patients Who participated previously on sectional study.The following data was collected : age, sex , and drugs used and Holter variables that demonstrated the presence of arrhythmias.Holter was performed in four stages: randomization , 2 , 6 and 12 months segments. The control group (CG) received medical treatment and intracoronary injection of placebo and the study group (SG) drug treatment and autologous stem cell implant. Results: There was no difference between EG and CG analyzing the criteria of arrhythmia. In the intra-group analysis, significant difference was found between the Holter tests study group in the variable of total ventricular ectopic compared with baseline, being between H1 and H2 p=0.014, between H1 and H3 p=0.004, between H1and H4 p=0.014. The variable non-sustained ventricular tachycardia between H1 and H3 with p = 0.036. Conclusion: The intracoronary injection of stem cells did not increase the incidence of ventricular arrhythmias in patients with Chagas cardiomopatia compared to the control group.